ORGANIZATIONAL FRAMEWORK FOR MANAGING THE EPIDEMIC PROCESS IN SALMONELLA INFECTION IN UZBEKISTAN - Мавлянов Ж. А.; Таджибаева Д. А. (Web of Journals Publishing, 2025)
The article discusses the organizational basis for managing the epidemic process in salmonella infection in Uzbekistan. Salmonellosis, called "diseases of civilization", are widespread all over the world, and at present we are talking not about the complete destruction of this infection, but about reducing the incidence rate. The paper analyzes the epidemiological features of salmonellosis in Uzbekistan, and also proposes a new system of epizootological and epidemiological surveillance. the need to strengthen the interaction between sanitary-veterinary and sanitary-epidemiological services for effective control and prevention of salmonellosis, as well as organizational measures for the prevention and control of infection.
Keywords: Salmonellosis, epidemiological process, epizootological surveillance, sanitary and veterinary service, sanitary and epidemiological service, prevention, infection.